61* - Steinberg, Hank.; Crystal, Billy; Jane, Thomas; Pepper, Barry, 1970-; Masur, Richard; McGill, Bruce, 1950-; Bauer, Chris; McDonald, Christopher, 1955-; Moffat, Donald, 1930-; Hall, Anthony Michael; HBO Films; Face Productions; et al. (New York, NY : HBO Home Video, 2001)
Mickey Mantle and Roger Maris, one was the Yankees' best loved players and the other was their most valuable. 1961 was about to be the summer that no one who loves baseball will ever forget. Both men find that they are approaching Babe Ruth's 1927 single-season 60 home-run record. Facing pressure from the media and the stands, both men know that there is only room for one winner. The fans make their choice, but the people's favorite isn't the favorite to win.
Special features include: Animated menus, chapter selections, cast & director bios, Making of 61* featurette, player bios & stats, 1961 home run list, original trailer.
Director of photography, Haskell Wexler ; editor, Michael Jablow ; music, Marc Shaiman ; costume designer, Dan Moore ; production designer, Rusty Smith.
Thomas Jane, Barry Pepper, Richard Masur, Bruce McGill, Chris Bauer, Chris McDonald, Donald Moffat, Anthony Michael Hall.
MPAA rating: Not rated.
DVD, English 5.1, English Dolby surround, Spanish stereo.
English or Spanish dialogue; English, French, or Spanish subtitles.
Keywords: Mantle, Mickey, -- 1931-1995 -- Drama; Maris, Roger, -- 1934-1985 -- Drama; New York Yankees (Baseball team) -- Drama; Baseball -- Records -- Drama; Feature films; Sports films; Video recordings for the hearing impaired